Penerapan Unmanned Aerial Vehicle (UAV) untuk Pengukuran Kuat Sinyal (Drive Test) pada Jaringan 4G LTE - Faisal Ahmad Ilham Nuari; Uke Kurniawan Usman; AT Hanuranto (Institut Teknologi Dirgantara Adisutjipto, 2021)
The work to get data directly from the field for optimizing a network is called drive test. The implementation of drive test by directly down to the field has several obstacles, such as the condition of the terrain is insufficient and risky to be passed by car. Barriers such as traffic congestion, risky environmental conditions and narrow road areas between buildings makes the implementation of drive test by using unmanned aerial vehicle (UAV) or known by drone. In this research, drive test is carried out on 4G LTE Network and uses an Android smartphone that has the G-NetTrack application installed. The Data parameters of the drive Test and QoS are searched. there are Reference Signal Receive Power (RSRP), Reference Signal Receiving Quality (RSRQ), Signal to Noise Ratio (SNR), delay and throughput. This research compares two methods, which are drive test with normal condition and drive test by using a UAV. The result of the drive test with normal condition is obtained an average value of RSRP -90.32 dBm, RSRQ -9.58 dB and SNR 3.99 dB. Whereas in the drive test by using UAV is obtained an average value RSRP -90.8 dBm, RSRQ 9.32 dB and SNR 4.77 dB. The results of this research showed that all parameters in comparison of both methods has meet the standard of Key Performance Indicator (KPI) with small value difference because drive test by using UAV is equals with normal drive test that is to know the real condition of obstacle in field.